Vol.2 - "Gupta, K. R. (ed.)" (New Delhi, 2006)
The United Nations was set up at the end of the Second World War, in 1945, to replace the ill-fated League of Nations. The United States, the United Kingdom, Russia (former USSR), France and China are permanent members of the Security Council, the most powerful organ of the United Nations. At that time, the United States was the most powerful country economically, technologically and militarily. It has been playing a dominant role in all decisions taken by the United Nations and its affiliated agencies. It has been dominating other countries and flouting the rules and provisions of the United Nations. To give a concrete example, the grant of loans by the World Bank, IMF and IFC is substantially influenced by the United States, instead of being guided by commercial and financial prudence. During the last six decades, the position of the world has substantially changed in regard to the economic, military and technological power. This has necessitated the redrawing of the United Nations and its various agencies. Unfortunately, this is being strongly resisted by the United States and other permanent members of the Security Council. The Volumes include viewpoints of the Secretary-General as well as all the important countries in regard to the reforms of the United Nations. They also include a large number of documents concerning these reforms. A detailed bibliography has been included to enable the inquisitive readers to pursue the subject further. The Volumes would be found highly useful by the students, researchers and teachers of Political Science and Economics. They would also be useful for executives and parliamentarians of all the countries concerned with the working of the United Nations and its agencies.
Keywords: United Nations-Reforms